Clinical therapy of platelet-rich plasma vs hyaluronic acid injections in patients with knee osteoarthritis: A systematic review and meta-analysis of randomized double-blind controlled trials. Issue 12 (26th March 2021) - Gong, Hao; Li, Kaiming; Xie, Rui; Du, Guoqing; Li, Linghui; Wang, Shangquan; Yin, Jing; Gu, Jinyu; Wang, Ping; Chen, Ming; Hou, Xiaozhou
Abstract: Objective: Knee osteoarthritis (KOA) is the most common degenerative disease of the joints caused by articular cartilage injury, degeneration of joint edges and hyperplasia of subchondral bone. The purpose of this study is to investigate the efficacy and safety of clinical therapy of platelet-rich plasma vs hyaluronic acid injections in patients with KOA. Methods: We systematically investigated Pubmed, Embase, and the Cochrane Library for all related articles published through May 2020. Any study was included that compared the effect of platelet-rich plasma (PRP) and hyaluronic acid (HA) in patients with KOA. The search terms included "platelet-rich plasma, " "PRP, " "hyaluronic acid, " "HA, " "knee, " "osteoarthritis, " "arthritis, " "KOA". Review Manager 5.3 was used to analyze and calculate data regarding these outcome indicators. Results: In this study, Six randomized double- blind controlled trials were included, including 338 patients in the PRP group and 323 patients in the HA group. Meta-analysis results showed that the Western Ontario and MacMaster Universities Osteoarthritis Index (WOMAC) Total Score was differed significantly between the PRP and HA groups at the 1, 6, 12 months follow-up (MD = 3.39, 95% CI: 2.85–3.92, P  < .05). In a comparison of Physical function scores at the 12 months follow-up, PRP improved knee function scores more than HA (MD = 3.28; 95% CI: 2.13–4.43; P  < .05). However, International Knee Documentation Committee (IKDC), Tegner Activity scores, EuroQol visual analogue scale (EQ-VAS), and Adverse Events (AEs) were all not significantly different ( P  > .05). Results showed that compared with HA, PRP had significant advantages in relevant improving knee function and quality of life. Conclusion: In improving knee function and quality of life, PRP showed superiority over HA in long-term follow-up from well-designed double-blind trials, but a large number of high-quality multi-center studies are still needed to provide more sufficient evidence.